Modeling and Simulation of Solar Systems Employing Collectors with Colored Absorber - Kalogirou, Soteris A.; Tripanagnostopoulos, Yiannis; Souliotis, Manolis (My University, 2004)
To avoid the monotony of the black colored flat plate solar collectors we can use absorbers of blue, red-brown, green or other color. Because of the lower collector absorptance these collectors have lower thermal efficiency than that of the usual black type collectors, they are however of more interest to architects for applications on traditional or modern buildings. In this paper applications of solar collectors with colored absorbers are presented and analyzed with respect to their performance, aiming to give guidelines for their wider use on buildings. These systems are simulated with TRNSYS on an annual basis at two different locations, Nicosia, Cyprus and Athens, Greece. The results show that the energy output depends on the absorber darkness. For a medium value of the coefficient of absorptance, the colored collectors give satisfactory results with respect to the drop of the amount of collected energy, compared to collectors with black absorbers. This implies the use of slightly larger collector aperture area to have the same energy output as that of typical black colored collectors.
Keywords: Solar collectors; Colored absorbers; Performance